Preserving the human character in an inhuman situation: the contributions and meanings of military soul care in the Swedish armed forces - Grimell, Jan (Frontiers in Psychiatry, 2025)
Military chaplains (MCs) are trained to address aspects of health beyond the remit of mental health professionals, namely the spiritual/religious and existential dimensions of service members’ mental health, within the biopsychosocial-spiritual (BPSS) model. Models of military spiritual care differ, and in Sweden this is termed Military Soul Care (militär själavård), regulated through the ACCES framework (Advisory role; Commander and Crisis support; Ceremonies; Education; Soul care conversations in absolute secrecy). The study aimed to explore the contribution and meaning that MCs attribute to Military Soul Care in the Armed Forces. A qualitative questionnaire was employed, extending earlier Swedish research while reaching broader scope and depth. Fifty MCs participated. Using an inductive approach, three overarching themes emerged: Preserving the human character in an inhuman situation, Sustaining ethical and moral dimensions and reflections in a military context and, Framing cultural coherence to assist meaning-making in a military context. While these findings resonate with the Swedish Armed Forces’ understanding and purpose of Military Soul Care, they highlight additional emphases that deepen the comprehension of its role. Recent research from the war in Ukraine underscores how sustaining the moral character of military personnel is vital, as the relentless brutality of war erodes the moral frameworks underpinning civilian identities and contexts of peace. This aligns closely with the concept of moral injury. Accordingly, the contribution and meaning of Military Soul Care should be recognized as extending far beyond a spiritual/religious function, constituting a holistic approach to mental health within the BPSS model. The Swedish model is existential rather than spiritual or religious, and inclusive rather than exclusive. As it is culturally embedded within specific Swedish traditions, frameworks, and understandings, it does not satisfactorily align with concepts such as ‘spiritual’ and ‘religious’. Future research is especially encouraged on sustaining the human character and advancing a culturally sensitive approach to military chaplaincy.